Tindak Tutur Perlokusi dalam Dialog Film Panggil Aku Ayah Karya Benni Setiawan - Hayati Tu Zahro; Prasetyo Yuli Kurniawan; Hany Uswatun Nisa (PT. Penerbit Tiga Mutiara, 2026)
Perlocutionary speech acts in film dialogue do not merely produce immediate responses but can drive changes in characters’ understanding, emotions, actions, and social relationships. This study aims to analyze the forms of perlocutionary acts, the contexts in which they occur, and the contribution of speech effects to changes in attitudes, actions, and social relationships in the film Panggil Aku Ayah by Benni Setiawan. The study employs a pragmatic approach and a descriptive qualitative method. Data consisting of utterances between characters were collected through observation, note-taking, documentation, and examination of scene contexts, and were analyzed through data condensation, data display, and conclusion drawing and verification. The findings identified 97 perlocutionary data, consisting of 31 directive acts, 28 assertive acts, 27 expressive acts, and 11 commissive acts. The speech effects comprised 41 affective, 36 cognitive, and 20 conative effects. The dominance of affective effects indicates that changes in emotions serve as an initial pathway toward changes in understanding and actions. The accumulation of these three effects transforms the relationships among Dedi, Tatang, and Intan from transactional relationships into familial bonds characterized by acceptance, affection, and trust.